GE_GERICHTE A/3252/2016 vom 24. Februar 2017 - GE Cour de justice (2017)
NOUEXP; IMMOBI | Recours interjeté au TF par le débiteur le 10 mars 2017, rejeté par ATF du 27 octobre 2017 ( | LP.97.1; ORFI.9.1